Discovery and Validation of a Recessively Inherited Major-Effect QTL Conferring Resistance to Maize Lethal Necrosis (MLN) Disease - Murithi, Ann; Olsen, Michael S.; Kwemoi, Daniel B.; Veronica, Ogugo; Ertiro, Berhanu Tadesse; L. M., Suresh; Beyene, Yoseph; Das, Biswanath; Prasanna, Boddupalli M.; Gowda, Manje (Frontiers in Genetics, 2021)
Maize lethal necrosis (MLN) is a viral disease with a devastating effect on maize production. Developing and deploying improved varieties with resistance to the disease is important to effectively control MLN; however, little is known about the causal genes and molecular mechanism(s) underlying MLN resistance. Screening thousands of maize inbred lines revealed KS23-5 and KS23-6 as two of the most promising donors of MLN resistance alleles. KS23-5 and KS23-6 lines were earlier developed at the University of Hawaii, USA, based on a source population constituted using germplasm from Kasetsart University, Thailand. Both linkage mapping and association mapping approaches were used to discover and validate genomic regions associated with MLN resistance. Selective genotyping of resistant and susceptible individuals within large F2 populations coupled with genome-wide association study identified a major effect QTL (qMLN06_157) on chromosome 6 for MLN disease severity score and AUDPC values in all three F2 populations involving one of the KS23 lines as a parent. The major effect QTL (qMLN06_157) is recessively inherited and explained 55% to 70% of the phenotypic variation with an approximate 6 Mb confidence interval. Linkage mapping in three F3 populations and three F2 populations involving KS23-5 or KS23-6 as one of the parents confirmed the presence of this major effect QTL on chromosome 6, demonstrating the efficacy of the KS23 allele at qMLN06.157 in varying populations. This QTL could not be identified in population that were not derived using KS23 lines. Based on the consistent and effective resistance afforded by the KS23 allele at qMLN06.157, the allele has been used extensively in both marker-assisted forward breeding and marker-assisted backcrossing schemes to improve MLN resistance of breeding populations and key lines for eastern Africa.